A fig deal: A global look at fig mosaic disease and its putative associates. - Preising, Stephanie; Borges, Darlan; de Queiroz Ambrósio, Márcia Michelle; da Silva, Washington L. (Plant disease, 2021)
Keywords: Badnavirus; Connecticut; Ficus; Phylogeny; Plant Diseases; dept.bio; peer-reviewed; phylogeny; plant disease

Detection of multiple grapevine viruses in New England vineyards - Borges, Darlan Ferreira; Preising, Stephanie; de Queiroz Ambrósio, Márcia Michelle; da Silva, Washington Luis (Crop Protection, 2020)
Vineyards in the New England region of the USA were surveyed for the occurrence of grapevine viruses. A total of ten vineyards were visited and 62 composite samples of leaves with the petioles were collected from symptomatic grapevines (Vitis spp.). All of the samples were assayed by double-antibody sandwich enzyme-linked immunosorbent assays (DAS-ELISA) using antibodies specific for four major grapevine leafroll-associated viruses (GLRaV-1, GLRaV-2, GLRaV-3, and GLRaV-4), grapevine fanleaf virus (GFLV), tobacco ringspot virus (TRSV), and tomato ringspot virus (ToRSV). Positive ELISA samples were further tested by reverse transcription polymerase chain reaction (RT-PCR) with primers specific for each of the viruses to confirm the ELISA results. Twenty-two samples were infected with at least one of the viruses tested. GLRaV-3 (24.19%) was the most prevalent virus detected followed by GLRaV-1 (12.90%), ToRSV (3.23%), and GLRaV-2 and TRSV (1.61%). This is the first study reporting on the presence of grapevine viruses in New England. Extensive surveys need to be conducted to evaluate the prevalence and economic impact of these viruses on New England vineyards. © 2020 Elsevier Ltd
Keywords: Grapevine fanleaf virus; Grapevine leafroll-associated virus 1; Grapevine leafroll-associated virus 3; Grapevine viruses; New England; Tobacco ringspot virus; Tomato ringspot virus; United States; Vineyards; Vitis; dept.bio; detection method; economic impact; pathogen; peer-reviewed; tobacco; vineyard; viral disease; virus

Lignin-derived carbon dots from leaf waste as sustainable plant sunscreens and UV-protective foliar coatings - Thangavelu, Raja; Gray, Sarah; Wu, Binlin; Pellegrino, Richard; da Silva, Washington; Zuverza-Mena, Nubia; Dimkpa, Christian; White, Jason (Environmental Science Nano, 2026)
Keywords: Agricultural waste; Agriculture; Carbon fibers; Lignin; Maple; Sustainable agriculture; Sustainable production; dept.phy